Algebraization and Optimization of Networked Evolutionary Boxed Pig Games with Passive Reward and Punishment. Issue 5 (23rd July 2018) - Wang, Jianjun; Zhao, Jianli; Fu, Shihua
Abstract: This paper investigates the evolutionary dynamics and optimization problem of the boxed pig games with the mechanism of passive reward and punishment by using the semi‐tensor product method. First, an algorithm is provided to construct the algebraic formulation for the dynamics of the networked evolutionary boxed pig games with the mechanism of passive reward and punishment. Then, the impact of reward and punishment parameters on the final cooperation level of the whole network is discussed. Finally, an example is provided to show the effectiveness of our results.